2022
DOI: 10.1136/bmjopen-2021-054230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of vision impairment and its association with cognitive impairment among older adults in India: a cross-sectional study

Abstract: ObjectiveThis study aimed to investigate the predictors of vision impairment in old age and how impaired vision is associated with cognitive impairment among the ageing population.DesignA cross-sectional study was conducted using a large country-representative survey data.Setting and participantsThis study used data from the ‘Building a Knowledge Base on Population Ageing in India’ survey, conducted in 2011. Participants included 9541 older adults aged 60 years and above.Primary and secondary outcome measuresT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…Our findings align with previous research indicating higher levels of loneliness among those who are more deprived (Madani et al, 2022) and those who perceive themselves as being less well-off when compared with others (Ayalon, 2019). Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b). Previous research using the LASI data has indicated that measures of food security are associated with measures of depression (Muhammad et al, 2022b; Patel et al, 2022), cognitive function (Kumar et al, 2021), and frailty (Muhammad et al, 2022a) in later life.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Our findings align with previous research indicating higher levels of loneliness among those who are more deprived (Madani et al, 2022) and those who perceive themselves as being less well-off when compared with others (Ayalon, 2019). Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b). Previous research using the LASI data has indicated that measures of food security are associated with measures of depression (Muhammad et al, 2022b; Patel et al, 2022), cognitive function (Kumar et al, 2021), and frailty (Muhammad et al, 2022a) in later life.…”
Section: Discussionsupporting
confidence: 57%
“…Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b). Previous research using the LASI data has indicated that measures of food security are associated with measures of depression (Muhammad et al, 2022b; Patel et al, 2022), cognitive function (Kumar et al, 2021), and frailty (Muhammad et al, 2022a) in later life. In our analysis, we find that a lack of food choice and a lack of food availability, including weight loss due to inadequate food consumption are associated with greater feelings of loneliness among those who work.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…And this association persisted among village participants, which may be due to the relative lack of medical resources and awareness, leading to an increased risk of cerebrovascular disease. A growing body of literature based on cross‐sectional and longitudinal data has shown that vision impairment is associated with cognitive decline among the older 30–32 . Changes in multiple measures of vision such as visual acuity, sensitivity, and visual processing speed have been observed among the aging population, and these changes have been associated with cognitive impairments 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The traditional factors on depression among the elderly are socio-demographic factors such as age, gender, marriage status, and level of education (Curran et al, 2020;Hubbard et al, 2021;Lotfaliany et al, 2019;Richardson et al, 2020;Wong et al, 2014), chronic diseases (Turana et al, 2021) and low-income (Anbesaw & Fekadu, 2022). Muhammad et al (2022) proved the strong relationship between food insecurity and depression among the elderly. Recent studies have begun to pay attention to digital competency variables as determinants of depressive symptoms in later life (Kuerbis et al, 2017; M. A.…”
Section: Introductionmentioning
confidence: 99%